Musculoskeletal biomechanics in cross-country skiing - Holmberg, L. J. (Linköping University Electronic Press, 2012)
Why copy the best athletes? When you finally learn their technique, they may have already moved on. Using muscluloskeletal biomechanics you might be able to add the "know-why" so that you can lead, instead of being left in the swells.